2022
DOI: 10.3390/biomedicines10092163
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in Voluntary Alcohol Intake and mRNA Coding for Synucleins in the Brain of Adult Rats Prenatally Exposed to Alcohol

Abstract: Maternal alcohol consumption is one of the strong predictive factors of alcohol use and consequent abuse; however, investigations of sex differences in response to prenatal alcohol exposure (PAE) are limited. Here we compared the effects of PAE throughout gestation on alcohol preference, state anxiety and mRNA expression of presynaptic proteins α-, β- and γ-synucleins in the brain of adult (PND60) male and female Wistar rats. Total RNA was isolated from the hippocampus, midbrain and hypothalamus and mRNA level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Females mating with one male were randomly divided into two groups. We used the model of forced (one-bottle) exposure to ethanol that we described earlier [22]: females in the experimental group drank a 10% ethanol solution as the only source of liquid throughout pregnancy. Control females consumed only water.…”
Section: A Model Of Prenatal Alcohol Exposurementioning
confidence: 99%
“…Females mating with one male were randomly divided into two groups. We used the model of forced (one-bottle) exposure to ethanol that we described earlier [22]: females in the experimental group drank a 10% ethanol solution as the only source of liquid throughout pregnancy. Control females consumed only water.…”
Section: A Model Of Prenatal Alcohol Exposurementioning
confidence: 99%
“…The obtained data clearly demonstrated that it was not the absence of any particular synuclein, but rather that a disbalance of synucleins caused widespread changes in the EEG spectral profiles. Research by Kokhan et al focused on studying the engagement of α-, β-, and γ-synucleins in mechanisms of craving for alcohol and developing alcohol dependence [ 14 ]. They described changes in the levels of expression in genes encoding for synucleins in the hippocampus and midbrain of alcohol-consuming male and female rats.…”
mentioning
confidence: 99%